Analysis of high‐resolution X‐ray computed tomography images of Bentheim sandstone under elevated confining pressures. (14th June 2016) - Saenger, Erik H.; Lebedev, Maxim; Uribe, David; Osorno, Maria; Vialle, Stephanie; Duda, Mandy; Iglauer, Stefan; Steeb, Holger
ABSTRACT: A sample of Bentheim sandstone was characterized using high‐resolution three‐dimensional X‐ray microscopy at two different confining pressures of 1 MPa and 20 MPa. The two recordings can be directly compared with each other because the same sample volume was imaged in either case. After image processing, a porosity reduction from 21.92% to 21.76% can be deduced from the segmented data. With voxel‐based numerical simulation techniques, we determined apparent hydraulic transport properties and effective elastic properties. These results were compared with laboratory measurements using reference samples. Laboratory and computed volumes, as well as hydraulic transport properties, agree fairly well. To achieve a reasonable agreement for the effective elastic properties, we define pressure‐dependent grain contact zones in addition to mineral phases in the digital rock images. From that, we derive a specific digital rock physics template resulting in a very good agreement between laboratory data and simulations. The digital rock physics template aims to contribute to a more standardized approach of X‐ray computed tomography data analysis as a tool to determine and predict elastic rock properties.